STRATEGI DIVERSIFIKASI PRODUK KAYU OLAHAN Acacia mangium (studi kasus : PT. Musi Hutan Persada) - Hamzah Hamzah; Marimin Marimin; Imam Teguh Saptono (School of Business, Bogor Agricultural University (SB-IPB), 2005)
The objective of this study is to suggest the best wood products of Acacia mangium that have high value-added as an alternative business and to formulate the fitting strategy. This study is descriptive case study applying purposive sampling method which involved wood product Experts and Senior PT. Musi Hutan Persada Management. Data have been analyzed through Exponential Compare Method (MPE) to select the best product alternative based on eleven set criteria, using AHP method, Hayami value-added Analysis, and Cost Analysis. The study shows that there are five superior Acacia mangium based products, namely 1) Sawnwood and woodworking (KGKO), 2) Furniture, 3) Medium Density Fibreboard (MDF), 4) Tannin-glue of Acacia mangium bark and 5) Wood Charcoal. And Sawnwood and Woodworking (KGKO), Furniture, and Tannin-glue have the best chance. Best business strategy to be adhered by MHP, “related-diversification”, then is to continue utilizing Acacia mangium wood as renewable resources, integrated and sustainable business.